The Normal of Peristalistic Waves In Vitro In The Small Intestine of Local Rabbits - Amelia Hana Amelia Hana (Jurnal Sain Veteriner, 2012)
local male rabbits aged 4 months, 1.0 to 1.5 kg body weight and healthy adaptation in individual cages with food and water ad libitum. All of rabbits were randomly divided into 2 groups: groups I (K-1) and II (K-2) eachof 4 head / group. All of rabbits fasted for 12 hours, and anesthetized with urethane 1.55 g/ kg bw in a 25% solution intraperitoneally. Each rabbit dissected, segments of small intestine (duodenum, jejunum, ileum) weretaken each 1.5 cm for the measured peristaltic wave. The K-1 group of rabbits were measured peristaltic wave using Physiograph and the K-2 with Kymograph. Physiograph or Kymograf operated after the specified time of 1 second and the impression of speed 10 mm/detik paper on the sensitivity of 0.1 and the sensitivity of the amplifier 50. During the calibration operation is often performed. Data obtained by the peristaltic waves (frequency and amplitude of contractions) small intestine for 5 minutes were analyzed by t test. The results of measurements of intestinal peristalsis by using Physiograph or Kymograf showed that the frequency and amplitude of peristaltic contractions of the proximal part is higher and more caudal direction tends to go down. Therefore it was concluded that the normal peristaltic waves of the small intestine to more caudal were getting less and less interm of the frequency and amplitude of peristaltic contractions.Keywords: rabbits,small intestine, peristaltic, physiograph, kymograph